Burnout, work engagement and work hours - how physicians' decision to work less is associated with work-related factors - FU Jung; E Bodendieck; M Bleckwenn; FS Hussenoeder; M Luppa; SG Riedel-Heller (BMC, 2023)
Abstract Background According to new estimates, the health care sector will suffer a shortage of physicians in primary and specialty care. In this context, work engagement and burnout are two constructs that have gained attention recently. The aim of this study was to investigate how these constructs are related to work hour preference. Method The present study was based on the baseline survey of the long-term study of physicians with different specialties, in which 1,001 physicians took part (response rate: 33.4%). Burnout was measured using the Copenhagen Burnout Inventory adapted for health care professionals; work engagement was assessed using the Utrecht Work Engagement scale. Data analyses included regression and mediation models. Results Overall, 297 out of 725 physicians were planning to cut down work hours. Several reasons - such as burnout - are discussed. According to multiple regression analyses desire to work less hours was significantly linked to all three dimensions of burnout (p < 0.001), as well as work engagement (p = 0.001). In addition, work engagement significantly mediated the relationship between the burnout dimensions on work hour reduction (patient-related: b = − 0.135, p < 0.001; work-related: b = − 0.190, p < 0.001; personal: b = − 0.133, p < 0.001 ). Discussion Physicians tending to reduce work hours exhibited different levels of work engagement as well as burnout (personal, patient- and work-related). Moreover, work engagement influenced the relationship between burnout and work hour reduction. Therefore, interventions that increase work engagement may positively impact negative effects of burnout on work hour changes.